Embracing technology for improving dental records and record keeping in the Republic of South Africa. A review. - Mahlangu, NT; Chandler, Susan; Sudi, Stephen (South African Dental Journal, 2023)
Forensic odontology (FO) techniques are used to identify unknown remains and play an integral role in dental-legal cases. The utility of FO relies on accurate antemortem records – the creation and management of which continues to be a global challenge, albeit more acutely presenting in developing countries. Inadequate record keeping and management by the dental fraternity has made application of FO techniques for identifying unknown remains challenging. In addition, dental-legal cases such as in homicides, rapes, patient mismanagement and fraud are sometimes unresolved due to record keeping and health system shortcomings. This current status quo affects families and society: bereaved families are deprived of closure, and protracted litigations ensue, leading to various socioeconomic consequences.